2013
DOI: 10.1371/journal.pone.0064896
|View full text |Cite
|
Sign up to set email alerts
|

Assessing SNP-SNP Interactions among DNA Repair, Modification and Metabolism Related Pathway Genes in Breast Cancer Susceptibility

Abstract: Genome-wide association studies (GWASs) have identified low-penetrance common variants (i.e., single nucleotide polymorphisms, SNPs) associated with breast cancer susceptibility. Although GWASs are primarily focused on single-locus effects, gene-gene interactions (i.e., epistasis) are also assumed to contribute to the genetic risks for complex diseases including breast cancer. While it has been hypothesized that moderately ranked (P value based) weak single-locus effects in GWASs could potentially harbor valua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 42 publications
2
36
0
1
Order By: Relevance
“…We found that SNP-SNP interactions between SNPs that did not exert individual effects on HCC risk were associated with HCC occurrence. Previous studies investigated SNP-SNP interactions during the development of breast cancer (Sapkota et al, 2013) and colorectal cancer (Goodman et al, 2006). These reports support our findings regarding the effects of SNP-SNP interactions on HCC risk.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found that SNP-SNP interactions between SNPs that did not exert individual effects on HCC risk were associated with HCC occurrence. Previous studies investigated SNP-SNP interactions during the development of breast cancer (Sapkota et al, 2013) and colorectal cancer (Goodman et al, 2006). These reports support our findings regarding the effects of SNP-SNP interactions on HCC risk.…”
Section: Discussionsupporting
confidence: 91%
“…Numerous studies have investigated the relations between cytokine polymorphisms and HCC risk; however, their results are controversial (Shin et al, 2003;Hirankarn et al, 2006;Slattery et al, 2007). Two studies have consistently noted that IL-1β-511 polymorphisms are significant risk factors for HCC progression in the Thai population and in Japanese patients (Tanaka et al, 2003;Hirankarn et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, SNPs may contribute to the genetic risk for BC, although their effect is usually only slightly statistically significant. In some studies, SNP-SNP interactions have been examined to evaluate epistatic effects contributing to BC [47] . SNPs in different DNA repair pathways, or in other pathways related to DNA metabolism, were selected, and specific SNP pairs showed a statistical association with BC risk.…”
Section: Resultsmentioning
confidence: 99%
“…Specific SNP pairs, selected within genes in DNA repair pathways or in other DNA metabolism pathways, showed a statistical association with BC risk [26]. Significant trends in BC risk were also observed in association with an increasing number of risk alleles in different DNA repair genes [27].…”
Section: Discussionmentioning
confidence: 96%